LEARNING EFFECTIVENESS THROUGH SOCIAL MEDIA AND AUDIOVISUAL IN PANDEMIC COVID – 19 - RONY ARAHTA SEMBIRING; SEPTIAN PANJAITAN (JURNAL ILMIAH KOHESI, 2021)
This research explores social media and audiovisuals as ways of optimizing English student learning. Given the developmentof media in information technology is so significant for education. Especially during this pandemic, the role of social mediaand audiovisuals deserves to be taken into account in student learning activities. The research focusing in identifying thelearning outcomes from Whatsapp as media that used by the students, the knowledge to determine the contribution of mediain the student learning, expand student knowledge, and provide opportunities for students to become innovative students.Descriptive qualitative method applied for the data analysis and comparative quantitative. The data was measured by usinginstrument, test and non-test. The research sample was taken from English students of English Literature study program atUniversitas HKBP Nommensen Medan and STP Bonaventura Deli Tua Medan, through 2 general subjects, namely learningmedia and educational statistics. The finding of the research have shown that the outcomes of the two classes did not showa meaningful difference. Furthermore, 24 questionnaire items showed that social media contributed more to student learningactivities than audiovisual media. Meanwhile, the research shows that students are more likely to behave negatively duringthe activities. They feel unsatisfy if the learning process are influenced totally by media. Addition the online learningimposition which needing a virtual learning process. So this research assumes that the existence of the media will beincreasingly felt if it is collaborated with other relevant learning methods.